Effects of root canal irrigations on intracanal medication with calcium hydroxide effects in root external resorption models. Issue 1 (April 2019) - Hisada, Akina; Nakamura, Koichi; Toyota, Yuki; Maeda, Ayako; Yoshihara, Toshihiro; Yawaka, Yasutaka
Abstract: Objective: The objective of the present in vitro study was to evaluate the influence of endodontic irrigation systems on the removal of smear layer and ion diffusion of calcium hydroxide through dentinal tubules in root external resorption models. Materials and methods: Forty single-rooted teeth were divided into four groups (G1, G2, G3, and G4) according to the irrigation regimens: G1, saline solution; G2, 10% sodium hypochlorite with ultrasonic irrigation; G3, 14% EDTA with ultrasonic irrigation; G4, 14% EDTA with ultrasonic irrigation → 10% sodium hypochlorite with ultrasonic irrigation. Ultrasonic irrigation lasted 45 seconds and all the roots were irrigated with 2 mL of saline solution. In experiment 1, the samples were observed on the root canal wall using scanning electron microscope and the percentage of opened dentinal tubules (POD) was calculated. Experiment 2 evaluated the diffusion of calcium ions through dentinal tubules. Results: In the middle region of root canals, the mean POD values were 0.11, 5.02, 82.17 and 96.72 in G1, G2, G3, and G4, respectively. In the apical region of root canals, the mean POD values were 0.06, 0.43, 4.41, and 12.70 in G1, G2, G3, and G4, respectively. The diffusion of calcium ions in G4 was significantly high in all groups. Conclusion: This study demonstrated that a combination of EDTA and sodium hypochlorite with ultrasonic irrigation was most effective in removing the smear layer and ion diffusion from the root canal to the surrounding media.